If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -4 = 65 Reorder the terms: -4 + 9x = 65 Solving -4 + 9x = 65 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9x = 65 + 4 Combine like terms: -4 + 4 = 0 0 + 9x = 65 + 4 9x = 65 + 4 Combine like terms: 65 + 4 = 69 9x = 69 Divide each side by '9'. x = 7.666666667 Simplifying x = 7.666666667
| 6+c=18 | | 3w+15=-4(w-2) | | 3w+15=-(w-2) | | 5-(1-x)=20 | | 7x+5y=-16 | | x=3(y/9) | | (4x^2+3x-5)(2x^3-10x+11)= | | 6x-15=6x | | 2x+7=10x+9 | | a-4/9a=-7/9 | | 1/2x^3-1/2x^2-24=0 | | 7=-2n-5 | | p(x)-750x^2+15000x=0 | | 0.8(25m-20n)= | | 5(2n-1)=5 | | -6+2t=3t-(6+5) | | 3x=y/9 | | ((d-4)/4)^2=49 | | -102=-6(8n+1) | | 2(3-6n)=102 | | 3[m+(-5)]=2m+10 | | 30+-10= | | 5-4(8x-2)=0 | | -5x+5(8x-6)=180 | | A=7/4 | | a+2=6a-6 | | 3t^3-30t^2-21t=0 | | 22=5a | | 13=3a+5-2a-7 | | -28=-28+v | | 6x+2x-16=-24 | | 40x+104=40x+80 |